Substrate integrated waveguide antennas and arrays - Debnath, Pampa; Chatterjee, Sayan (2017 1st International Conference on Electronics, Materials Engineering and Nano-Technology (IEMENTech), 2017)
At microwave and millimeter wave frequency, SIW technology is an emerging aspirant for the progress of antennas, circuits and components yielding a link between planar and non planar technology. Present study intends to provide an impression and exploitation of Substrate Integrated Waveguide (SIW) based antenna design subject to different structures, feeding mechanisms as well as performances. The performance enhancement technique has been compared and characterized by bandwidth enhancement, size miniaturization, and reduction of side lobe level and enhancement of gain. This overall discussion intends to present an idea of the recent progress in the modeling; development and realization of SIW based antenna design.